FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PEMERINTAHAN: GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA - S Syafruddin; N Nurdiansyah (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to determine the effect of leadership style, organizational culture, and work discipline on employee performance at the Regional Secretariat of Sumbawa Regency, either partially or simultaneously. The type of this study was associative. The data used is quantitative obtained from primary sources. The method used to collect primary data is a questionnaire. The total of population in this study was 35 people, so this study used census sampling. Data analysis tools were performed using multiple linear regression analysis techniques, t test, F test, and the coefficient of determination (R2) test. The results of this study showed that partially leadership style and organizational culture had no effect on employee performance at the Regional Secretariat of Sumbawa Regency, while work discipline had a positive and significant effect on employee performance at the Regional Secretariat of Sumbawa Regency. Than simultaneously leadership style, organizational culture and work discipline have a significant effect on employee performance at the Regional Secretariat of Sumbawa Regency. Variations in changes in the value of employee performance variables can be explained by the variables of leadership style, organizational culture and work discipline amounting to 70.9%, while the remaining 29.1% is influenced and explained by other variables not included in this study, such as work motivation, morale and well-being.